ТЕРМІНОЗНАВЧА КОНЦЕПЦІЯ І. ФРАНКА В СУЧАСНОМУ ВИМІРІ (Zaporizhzhia Historical Review, 2021)
In the article the terminological conception by I. Franko are investigated, the prospects of his terminological recommendations under the conditions of international contacts strengthening and integration of Ukraine into the European scientific space are motivated